"A Uniting Force:" Irish Music on U.S. Radio. Issue 1 (2nd January 2016) - Dempsey, John Mark; Geagan, Marc; Corbett, Rory
Abstract : Ethnic music of all kinds has had a powerful influence on American popular music throughout history, and this is certainly true of Irish music. For nearly 100 years, radio has been a vital conduit for conveying musical influences of all kinds to listeners and musicians alike. This qualitative study analyzes Irish radio broadcasting in the United States The article is based upon an open-ended survey of U.S. broadcasters of Irish music programs in the top 10 markets and provides a summary of their recent playlists.